Heavy Metals Distributions and Uptake in Field-Grown Maize after Application of Sewage Sludge in - Varavipour, Maryam; Givehchi, Saeid; Mashal, Mahmoud (Asian Journal of Chemistry, 2010)
The use of toxic metals in sewage sludge's applied to agriculture land in Iran to improve crop nutrition as well as to illustrate the metal behaviour in soils and plant up take is difficult to generalize, because it is strongly dependent on the nature of the metal sludge, soil properties and crop. Two year's field study was performed to evaluate heavy metal accumulation in the maize crop growing on clay-loam soil amended with waste water, to determine heavy metal up take and distribution in maize plants grown in this soil.